(untitled) (Educational Dimension, 2022)
In the article the formation of information and communication competence of future social workers is carried out. The sequence of topics studied by future social workers in the content part of the discipline of the information cycle "Modern information technology" is presented. The stages of ICT competence formation of future social workers are described. Authors provide a clear description of the sequence of learning and acquiring skills of practical work with a personal computer, cloud technology and its applications, free use of e-mail and additional features of Gmail, creating and formatting files of various formats, creating electronic educational resources by cloud technology, developing online courses and personal pages, understanding the capabilities and awareness of software for creating and processing various content by future social workers. They also analyze the benefits of the Moodle platform for its active use during the training of social professionals in the distance learning situation. These include: ease of use, intuitive interface for students and teachers, free, compliance with the requirements of higher education institutions for educational platforms, availability of methodological and reference materials, the ability to perform tests, planning and organizing the work of teachers and students and so on. In the article the need for skills and abilities to work with the above programs, services and technologies is emphasized too. The expediency of placing the discipline "Modern information technology" on the basis of the distance learning platform Moodle for future social workers is substantiated. The preconditions for the use of Moodle by the participants of the educational process are determined, the list of advantages and possibilities of this platform is given. The results (initial and final) of the study of the discipline "Modern information technology" are presented.